(untitled) (Journal of Universal Science Research, 2023)
Within the framework of the concept of Industry and 4.0, including IoT, the use of various sensors is increasingly widespread. It is necessary to understand that it is almost impossible to avoid so-called collisions (that is, overlaps) of signals. Such overlaps can and do lead to errors that can be quite significant. This article discusses the solution to the problem of identifying collisions, and also proposes an algorithm for avoiding such overlaps. The consequence of using this algorithm is to increase the noise immunity of the wireless network.